2015
DOI: 10.1002/ejlt.201400406
|View full text |Cite
|
Sign up to set email alerts
|

Differences in n‐alkane profiles between olives and olive leaves as potential indicators for the assessment of olive leaf presence in virgin olive oils

Abstract: The olive (Olea europaea) is one of the most important crops in the Mediterranean region for economic and culinary reasons. Cuticular waxes coat olives and olive leaves and play a significant role in plant physiology and resistance against environmental stresses. The present study describes n-alkane profiles in cuticular waxes of olives and leaves of three Italian varieties (Frantoio, Leccino and Maraiolo) during different stages of olive development. Additionally, the study investigates the differences betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…The occurrence of very low amounts of compounds at the high end of the homolog distribution suggested that they are formed merely as by-products of the normal wax biosynthesis machinery rather than through dedicated processes specific to their chain lengths. Characterization of enzymes involved in wax precursor elongation in respective species may reveal whether, in these cases, single FAEs indeed form both the ubiquitous chain lengths and the C 35+ homologs [ 2 , 6 , 23 , 39 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ].…”
Section: Extra-long Compounds In the Wax Mixtures Of Diverse Plantmentioning
confidence: 99%
“…The occurrence of very low amounts of compounds at the high end of the homolog distribution suggested that they are formed merely as by-products of the normal wax biosynthesis machinery rather than through dedicated processes specific to their chain lengths. Characterization of enzymes involved in wax precursor elongation in respective species may reveal whether, in these cases, single FAEs indeed form both the ubiquitous chain lengths and the C 35+ homologs [ 2 , 6 , 23 , 39 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ].…”
Section: Extra-long Compounds In the Wax Mixtures Of Diverse Plantmentioning
confidence: 99%
“…Consequently, olive leaf extract (OLE) may hold an even greater potential than EVOO for improving health outcomes. During EVOO processing leaves can unintentionally be left in the mixture if the separation methods are inadequate, alternately leaves can also be added to EVOO mixtures to provide health benefits and improve flavor [ 23 ]. The addition of leaves increase the phenolic and chlorophyll content of the oil but also the organoleptic traits as measured in volunteer taste tests [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…There was a depleting trend, even if the content of the last sampling of six out nine cultivars was higher than the last but one ( Table S14 ). In a study conducted in Tuscany (central Italy) on Frantoio, Moraiolo and Leccino cultivars, C31 was found to be the highest n -alkane in olive leaves, and was present in higher quantities in olive leaves than in olive fruits; this condition was repeated each month in samplings from July to November [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mihailova et al found C34 in higher quantities in olive leaves than in olive fruits throughout the whole ripening season; this happened also for C30, C32, C33 and C35. In brief, this condition was found for all the high-chain n -alkanes and, consequently, the oil extracted from batches of olive fruits containing a high leaf content showed a high n -alkane content [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation